The Internal Control & its Guidance for Prevent the Financial Corruption “ Practical Study in Controllers Sides” (مجلة المنصور, 2023)
The Internal Control in it is accounting concept is a tool of prevent and discover for financial affairs .It is from prevent side point of view updated the procedures for management which take place for prevent the financial frauds. From discover side it is done by specialized people and they have knowledge about the ways for release of the funds and it is confirmation and expenditure.All procedures and polices relate to the reliability of financial reporting timely feedback on the achievement of operational of strategic goals and compliance with laws regulations. From other side the Internal control refers to the actions taken to achieve a specific objectives(e.g., how to ensure the Organization payments to third parties are for valid services rendered).Internal Control procedures reduce process variation leading to more predictable outcome.Through the target meaning the internal control means the guide which prevent the financial deterioration which means take the funds with out of rights by cheating methods.From the above mentioned we conclusion that the internal officials will be with high skills and professional for signalize the errors and take care with discovery and prevent control For that internal control plays an important role in the prevention and detection of fraud.